Trauma-Informed Education in Open Online Courses: Lessons from Teacher Continuous Professional Development During COVID-19 - Watt, Caitlin; Krishnamoorthy, Govind; Ong, Sabrina; Rees, Bronwyn (International Review of Research in Open and Distributed Learning, 2025)
This study evaluates the feasibility and impact of the Open Online Course (OOC) aimed at enhancing teachers’ trauma-informed care practices during the onset of the COVID-19 pandemic. Educators from two public primary schools in Queensland, Australia, completed the course. Twenty-six educators were interviewed about their experience of the OOC. Thematic analysis revealed the feasibility of the OOC was influenced by participants’ ability to navigate the digital divide and allocate time for learning. The impact of the OOC was reflected in reports of the adoption of trauma-sensitive classroom management techniques amongst participants. The findings highlight that sustaining OOC-based teacher education on trauma-informed practice requires long-term access, integration of trauma-informed strategies, and ongoing support for hyflex and blended learning models. Findings are mapped onto a trauma-informed education framework and inform recommendations for future OOC design and delivery in post-pandemic educational settings.